Effectiveness of tranexamic acid on chronic subdural hematoma recurrence: a meta-analysis and systematic review - Pan, Wani; Hu, Jinyang; Huang, Xin; Jin, Erlang; Yao, Longfei; Han, Jing; Liu, Tiantian (Frontiers in Neurology, 2024)
Objectives Our objective was to compare the effectiveness of TXA in improving recurrence in patients with chronic subdural hematoma (CSDH). Methods Eligible randomized controlled trials (RCTs), prospective trials and retrospective cohort studies were searched in PubMed, Cochrane Library, Embase, and CNKI from database inception to December 2023. After the available studies following inclusion and exclusion criteria were screened, the main outcome measures were strictly extracted. Reman v5.4. was used to assess the overall recurrence rate. A random-effects model was used to assess pooled ORs, with the Mantel–Haenszel estimation method applied. Cochran Q (Chi-square) test and I2 statistics were used to assess inter-study heterogeneity. Funnel plots were used to evaluate publication bias. Results From the 141 articles found during initial citation screening, 9 literatures were ultimately included in our study. Our NMA results illustrated that patients with newly diagnosed Chronic subdural hematoma revealed a significantly improved recurrence rate when patients were treated with Tranexamic acid (OR: 0.33; 95% CI 0.26–0.41; p < 0.00001) compared with standard neurosurgical treatment. There was no significant difference in the incidence rates of thrombosis (OR: 0.84; 95% CI 0.63–1.12; p = 0.23) and mortality (OR: 1.0; 95% CI 0.57–11.76; p = 0.99), Occurrence of myocardial infarction was significantly less frequent in TXA users than in nonusers (OR: 0.18; 95% CI 0.04–0.82; p = 0.03). Conclusion TXA can effectively improve the recurrence rate of CDSH. It provides a high level of evidence-based medicine for clinical treatment. In addition, multicenter randomized controlled trials, with dose adjustments, are still needed to determine whether TXA intervention improves neurological function or prognosis.